Improvement of methods of compensating motion of dynamic objects in a video stream in a video conferencing system - Бараннік, В. В.; Бараннік, Д. В.; Сорокун, А. Д.; Дворський, М. В. (Science-based technologies, 2018)
The article deals with issues related to the speed of the video stream of video information, depending on the quality of video data required, from spatial resolution and frame rate. With the tendency of growth of volumes of video information and not providing the corresponding data volumes of the productivity of technologies of transmission and processing of video information in complexes videoconferencing - it is necessary to improve the coding methods. In order to increase the efficiency of management and operational activities, it is proposed to improve the existing methods of encoding a dynamic video stream object with algorithms for motion compensation for video conferencing in the control system.